A High-Quality Haplotype-Resolved Genome of Common Bermudagrass (Cynodon dactylon L.) Provides Insights Into Polyploid Genome Stability and Prostrate Growth - Zhang, Bing; Chen, Si; Liu, Jianxiu; Yan, Yong-Bin; Chen, Jingbo; Li, Dandan; Liu, Jin-Yuan (Frontiers in Plant Science, 2022)
Common bermudagrass (Cynodon dactylon L.) is an important perennial warm-season turfgrass species with great economic value. However, the reference genome is still deficient in C. dactylon, which severely impedes basic studies and breeding researches. In this study, a high-quality haplotype-resolved genome of C. dactylon cultivar Yangjiang was successfully assembled using a combination of multiple sequencing strategies. The assembled genome is approximately 1.01 Gb in size and is comprised of 36 pseudo chromosomes belonging to four haplotypes. In total, 76879 protein-coding genes and 529092 repeat sequences were annotated in the assembled genome. Evolution analysis indicated that C. dactylon underwent two rounds of whole genome duplication events, whereas syntenic and transcriptome analysis revealed that global subgenome dominance was absent among the four haplotypes. Genome-wide gene family analyses further indicated that homologous recombination-regulating genes and tiller angle-regulating genes all showed an adaptive evolution in C. dactylon, providing insights into genome-scale regulation of polyploid genome stability and prostrate growth. These results not only facilitate a better understanding of the complex genome composition and unique plant architectural characteristics of common bermudagrass, but also offer a valuable resource for comparative genome analyses of turfgrasses and other plant species.